Alquran Learning Model for Blind Students - Syumarlin Syumarlin; Mahyudin Ritonga; Syaflin Halim (Tarbawi Khatulistiwa, 2021)
Every Muslim has the right to receive Qur'an learning because the Qur'an as a way of life will not have an impact on Muslim life without starting with the ability to read and understand so that it comes to practice. Al-Quran learning for physically perfect people already has problems, even less for visually impaired people. Therefore, this study aimed to describe the Alquran learning model for students with special needs. This study was conducted using a descriptive approach. Data were collected through observation, interviews, and documentation studies. The data were analyzed through reduction, classification, interpretation to the conclusion. Based on the results, Alquran learning methods for blind students were lecture, question, and answer, discussion, sorongan, bandongan, and drill, while Alquran learning media for blind students were braille, reglet and stylus, Alquran Audio, and Digital Alquran.